In the Hands of Humanity: Creation, Conservation and Degradation of the World among the Chibcha - Niño Vargas, Juan Camilo (Revista Española de Antropología Americana, 2025)
One of greatest contributions of anthropology has been to reveal alternative ways of conceiving and inhabiting the world, which differ from those currently dominant, thereby exposing the contingent and exceptional nature of the latter. As part of this endeavor, this paper explores the ideas and practices of the Chibchan peoples of the Isthmo-Colombian area regarding the centrality of human beings and the processes of humanization and dehumanization through which they render the world a livable place. At the heart of the discussion are notions of creation, conservation and destruction derived from their mythological thought and cosmo-ecological practices. This exercise on comparative ethnology promises to enrich our knowledge of the Chibchan peoples and the Isthmo-Colombian region, while also laying the groundwork for new critical perspectives on modern anthropocentrism associated with the present-day planetary crisis.